Crikey steveirwini gen. et sp. nov. from montane habitats in the Wet Tropics of northeastern Queensland, Australia (Gastropoda: Eupulmonata: Camaenidae) - Stanisic, John (Zootaxa, 2009)
Crikey steveirwini gen. et sp. nov. is described from montane habitats in the Wet Tropics of northeastern Queensland, Australia. This species is unique among the eastern Australian arboreal camaenids in both distribution (confined to montane refugia), and genital morphology (lacking a penial verge). An assessment of the phylogenetic position of C. steveirwini is made based on a combination of morphological features (shell and anatomy) and available molecular data. The biogeographic implications for the Australian camaenid radiation of this altitudinally restricted species are briefly discussed.